Open repair of type III endoleak with preservation of the endograft for a ruptured abdominal aortic aneurysm after endovascular aneurysm repair - Bellamkonda, Kirthi (J Vasc Surg Cases Innov Tech, 2020)
Abdominal aortic aneurysm rupture after endovascular aneurysm repair (EVAR) is rare, but remains a significant limitation of endovascular technology. Preservation of the endograft during open conversion of a post-EVAR rupture has been shown to be associated with improved perioperative outcomes. An interposition Dacron graft with felt pledgets is a novel bail-out option for the open reconstruction of a type III endoleak with total endograft preservation. This technique is useful in high-risk patients presenting with ruptured abdominal aortic aneurysm after EVAR and no clear source of endoleak.